Musculoskeletal System Problems in Dental Practitioners - Cakir, Mustafa (Eurasian Journal of Family Medicine (Online), 2022)
Aim: In this study, it was aimed to evaluate the musculoskeletal system problems encountered by dentists working in an oral and dental health center in Kocaeli, Turkey. Methods: This cross-sectional study including 74 dental practitioners was carried out in 4 Oral and Dental Health Centers in Kocaeli between 15-31 January 2020. A questionnaire was used for data collection. The questionnaire consisted of two sections. The first section concerned the sociodemographic characteristics of the subjects whereas the second section consisted of the Extended Nordic Musculoskeletal Questionnaire. Descriptive statistics are presented as mean (±) standard deviation, frequency distribution, and percentage. The Chi-square test was used to compare categorical variables. Results: In the study, 70.3% of the subjects were female, 40.5% were aged over 41 years of age, and the average age was 38.1±9.4 years. It was determined that 78.4% of the dental practitioners reported pain in their necks, 50.0% in their shoulders, 67.6% in their backs, 63.5% in wrists and hands, and 68.9% in their lower backs. Moreover, the participants reported experiencing pain severe enough to affect their personal or work lives within the last 12 months in their necks (44.6%), shoulders (23.0%), backs (33.8%), hands and wrists (41.9%), and lower backs (43.2%). Conclusion: In the study, it was found that dentists have a high frequency of musculoskeletal problems. It is recommended that dentists work in a seated position and exercise between studies. Keywords: dentists, musculoskeletal diseases, ergonomics